Nanomaterial-Based Drug Delivery Systems for Pain Treatment and Relief: From the Delivery of a Single Drug to Co-Delivery of Multiple Therapeutics - Yuhang Xu; Xingpeng Dong; Heming Xu; Peifu Jiao; Lin-Xia Zhao; Gaoxing Su (MDPI AG, 2023)
The use of nanomaterials in drug delivery systems for pain treatment is becoming increasingly common. This review aims to summarize how nanomaterial-based drug delivery systems can be used to effectively treat and relieve pain, whether via the delivery of a single drug or a combination of multiple therapeutics. By utilizing nanoformulations, the solubility of analgesics can be increased. Meanwhile, controlled drug release and targeted delivery can be realized. These not only improve the pharmacokinetics and biodistribution of analgesics but also lead to improved pain relief effects with fewer side effects. Additionally, combination therapy is frequently applied to anesthesia and analgesia. The co-encapsulation of multiple therapeutics into a single nanoformulation for drug co-delivery has garnered significant interest. Numerous approaches using nanoformulation-based combination therapy have been developed and evaluated for pain management. These methods offer prolonged analgesic effects and reduced administration frequency by harnessing the synergy and co-action of multiple targets. However, it is important to note that these nanomaterial-based pain treatment methods are still in the exploratory stage and require further research to be effectively translated into clinical practice.